1988
DOI: 10.1002/ddr.430150108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of vinpocetine, vincamine, and nicergoline on the normal and hypoxia‐damaged learning process in spontaneously hypertensive rats

Abstract: Vinpocetine (CavintonB), vincamine, and nicergoline (SermionB) were evaluated for the ability to protect cognitive function of spontaneously hypertensive rats from the damaging effect of hypoxia. Normobaric hypoxia (6% oxygen) was applied during the acquisition of a two-way active avoidance task (3 sessions, 50 trialsisession). Hypoxia decreased the percentage of conditioned avoidance responses by 50% on day 3. Vinpocetine (1.25-1 0 mg/kg) administered orally 60 min prior to the daily sessions did not signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Groo et al 15 used spontaneously hypertensive rats (SHRs) to study avoidance response to hypoxia as they were reported to be more sensitive to stressful stimuli 58,59 and showed greater hypoxic vulnerability than normotensive Wistar rats. The SHRs were exposed to either NH (6% oxygen) or normoxic conditions.…”
Section: Hypoxia and Memory Impairment In Ratsmentioning
confidence: 99%
“…Groo et al 15 used spontaneously hypertensive rats (SHRs) to study avoidance response to hypoxia as they were reported to be more sensitive to stressful stimuli 58,59 and showed greater hypoxic vulnerability than normotensive Wistar rats. The SHRs were exposed to either NH (6% oxygen) or normoxic conditions.…”
Section: Hypoxia and Memory Impairment In Ratsmentioning
confidence: 99%
“…Many previous studies used hypoxic chamber set at 6-8% of oxygen content for a shorter period of time and found significant memory deficit. 47,48 Lowering the oxygen contents of inspired air to 6% impaired acquisition of the avoidance response, and the difference between the performance (percentage of avoidance responses) of animals kept under normoxic and hypoxic conditions was significant on day 3 (69.2% and 38.0% conditioned avoidance response, respectively). This finding was in line with earlier study findings by Saligaut et al, 47 where the acquisition of a conditioned avoidance response was impaired under 300 torr hypobaric hypoxia (8% oxygen content).…”
Section: Figures 3-8 U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…Further clinical investigations have helped to clarify the effectiveness in mental impairment (Battaglia et Heidrich, 1985; Kuglerand Meurer-Krue/~1985) and multi-infarct dementia (Saletu et al, 1987b). Recent preclinical findings have been presented by Groo et al (1988), Voroninaet al, (1988) and Nikolovet al (1987).…”
Section: Vincamine-type Compoundsmentioning
confidence: 96%
“…They display significant effects on cerebral circulation. Pharmacology (Groo et al, 1988;Szpomy, 1977;Witzmann et al, 1977), influence on sleep pattern (Glatt et al, 1978) aI., 1981). For recent animal data on arecoline see Rood et aI.…”
Section: Vincamine-type Compoundsmentioning
confidence: 99%